Development of the Website based Chemistry Learning Integrated Evaluation To Measure Students Learning Interest In Colloids Material (Journal of Innovative Science Education, 2020)
The development of technology is currently one of the demands for teachers and prospective teachers to be able to create learning media that appeals to students so that students have an interest in learning. The use of the web-based learning media integrated with evaluation can be one of the solutions in chemistry learning. The purpose of this research is to know the validity and response of students about learning media developed. The development model used in this research is the ADDIE model. The validation of the development product is done by the validator of media experts and chemical material experts, while the trial is conducted by 29 students of class XI IPA 2. The analysis results of the validator state that the quality of the learning media belongs to a very good category with a percentage of 92.78% of the media expert and 83.34% of the material experts. Students ' learning interest percentage of 72.12% is in good category. Learning Media developed in the form of websites integrated with the evaluation of CBT (computer bassed test). The development of learning media contains material in the form of power point slides, learning videos, training of CBT exercises, student presences and student profiles whose functions for students to see the results of training and evaluation. Keywords: Computer Based Test, Learning Media, Website